Interpretação e decisão judicial na tradição hermenêutica brasileira: uma compreensão a partir do in claris cessat interpretatio - Rocha, Matheus Alves da (Universidade do Vale do Rio dos Sinos, 2025)
The present dissertation sought to analyze the problem of in claris cessat interpretatio, which can be translated into the possibility of texts being interpreted literally. A review of the various theories of law that have emerged since the codification movement reveals significant shifts in the freedom of the interpreter and the tension between understanding/interpretation. This work investigates the Brazilian legal tradition, with a focus on the legal hermeneutics developed by some authors, particularly in the context of formal interpretation and its limits. The research will concentrate on four Brazilian authors, representative of different theoretical and political contexts: Francisco de Paula Baptista, Carlos Maximiliano, Alípio Silveira, and Lenio Luiz Streck. Utilizing the tenets of hermeneutic phenomenology, a methodological framework is employed to deconstruct their theses, thereby facilitating the identification of continuities and ruptures in the conceptualization of judicial subjectivity. It is imperative to acknowledge that a fundamental aspect of this work is the necessity of comprehending the past in order to facilitate a more profound understanding of the present. The present study offers a contribution to the existing discourse on Neoconstitutionalism by exploring the potential of Brazilian tradition to inform discussions on the subject. This exploration encompasses the critique of the “Culture of Precedents”, that was inaugurated by the 2015 Code of Civil Procedure, as well as the Brazilian Legal Realism or the Jurisprudentialization of law. Therefore, the objective of this research is twofold: first, to enhance comprehension of the authors who have exerted influence on Brazilian legal hermeneutics; and second, to advance towards a more nuanced understanding of the relationship between text and interpreter.
Keywords: Tradição jurídica; Hermenêutica; Formalismo interpretativo; Compreensão; Legal tradition; Hermeneutics; Interpretive formalism; Understanding; ACCNPQ::Ciências Sociais Aplicadas::Direito